2011
DOI: 10.3390/coatings1010017
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Characterization of High Velocity Oxy-fuel Sprayed Coatings: Techniques, Materials, and Applications

Abstract: Abstract:In this work High Velocity Oxy-fuel (HVOF) thermal spray techniques, spraying process optimization, and characterization of coatings are reviewed. Different variants of the technology are described and the main differences in spray conditions in terms of particle kinetics and thermal energy are rationalized. Methods and tools for controlling the spray process are presented as well as their use in optimizing the coating process. It will be shown how the differences from the starting powder to the final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
93
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(100 citation statements)
references
References 73 publications
(123 reference statements)
1
93
1
5
Order By: Relevance
“…The presented and analyzed result showed that the coating obtained by hybrid spraying method had got the correct structure with a thickness of about 550 mm. Testing of micro-jet-cooled coatings, presented in this paper and in [2][3][4][5] showed substraty hardness and microporosity improvement over HVOF sprayed coatings samples, while bond strength, coating microhardness, and abrasion resistance of the hybrid-sprayed coatings were essentially unchanged.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The presented and analyzed result showed that the coating obtained by hybrid spraying method had got the correct structure with a thickness of about 550 mm. Testing of micro-jet-cooled coatings, presented in this paper and in [2][3][4][5] showed substraty hardness and microporosity improvement over HVOF sprayed coatings samples, while bond strength, coating microhardness, and abrasion resistance of the hybrid-sprayed coatings were essentially unchanged.…”
Section: Resultsmentioning
confidence: 98%
“…Based on published results, it can be concluded, that the obtained coatings have got different properties, despite the similar chemical composition . The decisive role played [1][2][3][4][5][6][7][8] At first, the energy (supplied during the spraying process) forms a kind of phases in the coating material. The technology of spraying has got significant role in the forming process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] Each of these techniques utilises different thermal spray torches, giving rise to different particle temperatures and velocities. [4] This has significant effects on coating microstructure and phase composition, which in turn affects coating photoactivity. There have been a number of papers which compare the photocatalytic properties of HVSFS and SPS TiO2 coatings.…”
Section: Introductionmentioning
confidence: 99%